Destined to Melancholy. Emotions in Contemporary Women’s Croatian Poetry - Gawałkiewicz, Zuzanna (Poznańskie Studia Slawistyczne, 2015)
The aim of the study is to answer the question what the postmodern melancholy is and how it manifests itself through emotions in contemporary works of selected Croatian poets: Božica Zoko, Marijana Radmilović and Tea Gikić. The analysis of poems focused on the theme of body language and metaphors associated with physicality, which are culturally consistent way of ex pressing melancholy. Postmodern phenomena, such as consumerism, media development, twilight of grand narratives, transformation of the aesthetics of the text, expansion of popular culture or value system instability, which create a melancholic anxiety. Characteristics of postmodern melancholy language have been analyzed which is also the language of women’s depression. The theme, most often undertaken by poets, turned out to be the body and language.